PEOPLE'S PERCEPTION OF THE SPREADING NEWS HOAX ON RESIDENTS HAS BEEN AFFECTED BY THE COVID-19 OUTBREAK IN THE VILLAGE PERCUT SEI VILLAGE - Buyung Solihin Hasugian; J. Prayoga; Ananda Hadi Elyas (Universitas Dharmawangsa Medan, 2023)
ABSTRACTThe spread of the corona virus, otherwise known as the covid-19, is growing, as news of its origin (hoax) spreads into the citizen timeline +62. Her comments ranged from netizens' upload that makassar's citizens were positive about corona so that it could be spread by air that is disrupting the media sanity. Not only physical and mental health but also mental health. Our daily activities must also be wholesome and aberrant behavior to be avoided. As with the media, media mental health is something to be respected. Failure to receive and process information from many different time lines can easily lead to disaligned channels, leading to user psychology that may be affected.The long-term objective of this study is to produce and provide information to the public, especially so that news may not be easily swayed. Many people, after hearing false reports, quickly conclude that the news is true. Therefore, the purpose of this study is not to analyze people's perceptions as well as to know how their perceptions in response to and receiving news hoaxes in society. The study also detracts from public perception, especially from people's negative assessments of lies that they often hear and receive. The public will learn to digest the news well by seeking information from other media. As more and more hoaxes, more and more information is revealed.The study will be done in the village office of ponds. The method used was qualitative method, a random selection of sample data sources. Sample data source identification, the proposal is still preliminary and will be developed further by field researchers. The main data-gathering techniques are observation, in-depth interviews, library studies, and a combination of all three or cross-examination. Thus, overcoming the completeness of data while doing research will require planning to examine the validity of the data.Keyword: spread, news, hoax, covid-19